Politicians' email communication with voters: A field experiment for the 2021 Bundestag elections. - Ekkehard A Köhler; Marius D May (PLoS ONE)
First-time voters hold polarized views on migrant issues. Few is known about how politicians react to this peculiar phenomenon in democracies. This paper studies whether rational behavior drives political elites' response behavior in a RCT email responsiveness study. We contacted 1554 candidates for the German Bundestag shortly before the 2021 election and asked about their stance on dual citizenship. We went into the field as first-time voting high-school students and varied their stances on dual citizenship, migration backgrounds and genders. Introducing a theoretical framework based on the single-policy task model and supplementing it with costly persuasion, we are able to disentangle and test for partisanship and opportunism. Our main results are as follows: First, both partisanship and opportunism explain the candidates' response behavior. Second, candidates exert more effort if they disagree with a voter than if they agree with a voter.